Non-human Primate Models to Explore the Adaptive Mechanisms After Stroke - Higo, Noriyuki (Frontiers in Systems Neuroscience, 2021)
The brain has the ability to reconstruct neural structures and functions to compensate for the brain lesions caused by stroke, although it is highly limited in primates including humans. Animal studies in which experimental lesions were induced in the brain have contributed to the current understanding of the neural mechanisms underlying functional recovery. Here, I have highlighted recent advances in non-human primate models using primate species such as macaques and marmosets, most of which have been developed to study the mechanisms underlying the recovery of motor functions after stroke. Cortical lesion models have been used to investigate motor recovery after lesions to the cortical areas involved in movements of specific body parts. Models of a focal stroke at the posterior internal capsule have also been developed to bridge the gap between the knowledge obtained by cortical lesion models and the development of intervention strategies because the severity and outcome of motor deficits depend on the degree of lesions to the region. This review will also introduce other stroke models designed to study the plastic changes associated with development and recovery from cognitive and sensory impairments. Although further validation and careful interpretation are required, considering the differences between non-human primate brains and human brains, studies using brain-lesioned non-human primates offer promise for improving translational outcomes.